Heat tolerance, thermal equilibrium and environmental management strategies for dairy cows living in intertropical regions - Santos, Severino Guilherme Caetano Gonçalves dos; Saraiva, Edilson Paes; Gonzaga Neto, Severino; Maia, Maria Isabelly Leite; Lees, Angela M.; Sejian, Verassamy; Maia, Alex Sandro Campos; Medeiros, Geovergue Rodrigues de; Fonsêca, Vinícius de França Carvalho (Frontiers in Veterinary Science, 2022)
This review makes an attempt to characterize the physical attributes of heat tolerance, thermal equilibrium and thermal stress thresholds for dairy cows living in tropical environments, with a particular emphasis on pasture-based systems. Under such circumstances, the radiant heat load is the principal climatic factor that determines rates of heat and mass exchanges between cows and the environment. This fact may explain why simple mechanistic models based on air temperature and humidity are not adequately predicting thermal stress thresholds for cattle in tropical regions. To overcome this limitation, the Index of Thermal Stress for Cows (ITSC) and Index for the time spent in shade (ITS), which account for various sources of thermal radiation, were proposed to predict autonomous and behavioral thermoregulation of cows. Overall, the evolutionary adaptation of cattle in tropics favored animals that have cutaneous surface with a skin well protected against penetration of ultraviolet solar radiation (UV), covered by a coat surface with high thermal conductivity. For Holstein breed, although predominantly black animals absorb greater levels of short-wave solar radiation, they may present better protection of skin than white ones. However, dark-colored cows in tropical pastures have potential to absorb as much as 640 W m-2 of thermal radiation. This amount of heat load would require close to 1300 g h-1 of cutaneous evaporative water loss through sweating to prevent increases to body temperature, where cows do not have access to shade. Indeed, cows are motivated to reduce time spent grazing and to seek shade when solar irradiance exceeds 550 W m-2, levels that in equatorial latitudes are likely to occur between 08:00 and 16:00h. This information may help producers improve the welfare of cows, as they can determine more comfortable hours for them to graze, for example, by employing nocturnal grazing. Over the daytime, cows should have access to areas with shade and this could include shade provided via solar panels, which has the potential to improve thermal comfort and sustainability of dairy production in tropical areas.